Virtualization An Emerging Technology A Technology Overview (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Virtualization is one of the hottest trends in information technology today. This is no accident. While a variety of technologies fall under the virtualization umbrella, all of them are changing the IT world in significant ways. This paper introduces Microsofts virtualization technologies, focusing on three areas: hardware virtualization, presentation virtualization, and application virtualization. Since every technology, virtual or otherwise, must be effectively managed, this paper also looks at Microsofts management products for a virtual world. The goal is to make clear what these offerings do, describe a bit about how they do it, and show how they work together.